If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 1)(2x + -1) = 0 Reorder the terms: (1 + 2x)(2x + -1) = 0 Reorder the terms: (1 + 2x)(-1 + 2x) = 0 Multiply (1 + 2x) * (-1 + 2x) (1(-1 + 2x) + 2x * (-1 + 2x)) = 0 ((-1 * 1 + 2x * 1) + 2x * (-1 + 2x)) = 0 ((-1 + 2x) + 2x * (-1 + 2x)) = 0 (-1 + 2x + (-1 * 2x + 2x * 2x)) = 0 (-1 + 2x + (-2x + 4x2)) = 0 Combine like terms: 2x + -2x = 0 (-1 + 0 + 4x2) = 0 (-1 + 4x2) = 0 Solving -1 + 4x2 = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 4x2 = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 4x2 = 0 + 1 4x2 = 0 + 1 Combine like terms: 0 + 1 = 1 4x2 = 1 Divide each side by '4'. x2 = 0.25 Simplifying x2 = 0.25 Take the square root of each side: x = {-0.5, 0.5}
| x^2+4x+a^2-3a=0 | | 2x(4x^2+3x-5)=y | | 10(t-5)+8=6(3t+3)-11 | | 4x^2+4x+37=0 | | 100000+30Q=150000+20Q | | 10000+30Q=150000 | | 7x^4=448x | | x^3+2x^2-25x+50=0 | | X^2+4xy+4y^2=0 | | 9x-4y=56 | | x+8=2x-6 | | 4x=-3+21 | | 5(x-8)=3(x-6) | | -5.2(2p+4)-1.3(3p-5)= | | 5x+3y=52 | | ln(x)+ln(4)=2 | | 0.33(6x-8)=0.66(5x-2)+9 | | 2y+7x=-10 | | .375x-4=4x | | 2s-13=-31+5s | | 8y-27=-55+y | | 3x^2+12x-3y^2+18y-14=0 | | -7x-7x=-112 | | 4(x+2)=10+3x | | 3x^2+12x-3y^2+18y=14 | | 7x+10x=136 | | -4x-20=-84 | | -4x-20=84 | | x+(x+1)(x+2)=27 | | -82=8+9x | | 9x^2+3=12x | | x^3-3x^2+3=0 |